Evaluation of different control schemes for load frequency control (LFC) in synchronous generators - Tay Chai, Ci Hong (2018)
In an ideal power system operation, the system frequency is always maintained constant at nominal value of 50Hz by applying the load frequency control (LFC) on the synchronous generators. The main function of LFC is to reduce the frequency deviation to zero by adjusting the no-load speed setting of the synchronous generators so that the system frequency is always maintained at the nominal value. In the Clean Energy Research Laboratory (CERL) located at S2-b7c-05, a 13.5kVA synchronous generator has been interfaced with the microgrid testbed. An existing LFC module based on a simple feedback control loop has been developed. The objective of this project is to study the effect of Model Predictive Control (MPC) and Proportional-Integral-Derivative (PID) control based LFC on synchronous generator by using the LabVIEW program. The final results of both controllers obtained in the real system experiment will be discussed. Further improvement of the program will also be discussed in the conclusion.